Photoelectron circular dichroism in angle-resolved photoemission from liquid fenchone. Issue 14 (7th March 2022) - Pohl, Marvin N.; Malerz, Sebastian; Trinter, Florian; Lee, Chin; Kolbeck, Claudia; Wilkinson, Iain; Thürmer, Stephan; Neumark, Daniel M.; Nahon, Laurent; Powis, Ivan; Meijer, Gerard; Winter, Bernd; et al.
Abstract : We present the first X-ray photoelectron circular dichroism (PECD) study from a liquid phase sample, exemplified for liquid fenchone at the C 1s edge. Abstract : We present an experimental X-ray photoelectron circular dichroism (PECD) study of liquid fenchone at the C 1s edge. A novel setup to enable PECD measurements on a liquid microjet [Malerz et al., Rev. Sci. Instrum., 2022, 93, 015101] was used. For the C 1s line assigned to fenchone's carbonyl carbon, a non-vanishing asymmetry is found in the intensity of photoelectron spectra acquired under a fixed angle in the backward-scattering plane. This experiment paves the way towards an innovative probe of the chirality of organic/biological molecules in aqueous solution.